Theaetetus 151e–186e: Did Plato Refute Protagoras? - Calenda, Guido (Peitho. Examina Antiqua, 2024)
In the Theaetetus, which seeks a definition of knowledge, the first definition of Theaetetus, namely that ‘knowledge is perception’, is easily refuted without the need to refer to Protagoras. But for Plato the refutation of Protagoras is a goal in itself, and he devotes almost half the dialogue to this task. He argues that the doctrine of homo mensura amounts to saying that ‘all judgements are true’ and, using his ‘most exquisite argument’, he claims to prove that it is self-refuting. As many scholars have recognised, this alleged demonstration depends on the arbitrary dropping of the relativistic qualifier that specifies ‘for whom’ a given judgement is true. Plato does not justify the disappearance of the qualifier, but rather tries to disguise it. Indeed, Protagoras has an epistemological conception that is opposed to Plato’s theory of knowledge and that is fundamental to the logical justification of the political conceptions set out in the Republic. For Plato, therefore, the refutation of Protagoras’ doctrine of homo mensura is an imperative ethical requirement. He is not too demanding in his choice of arguments: he does not seek rigour in argumentation, only persuasive effectiveness – more than two millennia of interpretations have proved him right.